Was Samson a Promiscuous Man (Judges 13-16)? Viewing Samson as a Human Figure in a Theoretical Approach - Ottuh, John Arierhi (NIU Journal of Social Sciences, 2019)
This paper discusses the character of Samson as an historical figure within Judges 13-16 narratives in the Old Testament Bible. The main aim of this paper is to find out through theoretical inference whether there were circumstances surrounding Samson’s sexual behaviour. Drawing from causal theory, the paper argues that there is a possible nexus between Samson’s failed marriage and his subsequent relationship with other women. It shows that Samson’s problem was not metaphysical but human induced and as such it is causal. It constructs, Samson as human figure in the narrative and analyses the text from the perspective of causal theory and concludes that Samson’s failed marriage could be responsible for his subsequent relationship with a Harlot in Gaza and Delilah. In the Narrative, apart from the harlot in Gaza, the ex-wife and Delilah betrayed his love. Within this line of theoretical thought, Samson was seen as a victim of emotional catharsis, human intrigue, insensitivity, naivety and the woman power factor. Key Words: Samson, Causal theory, Promiscuity, Judges 13-16, Human figure,